What is Buddhist enlightenment? - Wright, Dale Stuart (Oxford University Press, 2016)
Dale Wright offers a wide-ranging exploration of issues that have a bearing on the contemporary meaning of enlightenment. He considers the historical meanings of enlightenment within various Buddhist traditions, but does so in order to expand on the larger question that our lives press upon us-what kinds of lives should we aspire to live here, now, and into the future?